Determination the Level of Complement Protein C3 and C4 in Gastric Ulcers Patients in Baqubah City, Iraq - Maha Falh Nazzal; Ashwaq Muthanna Whaeeb (Diyala Journal of Medicine, 2018)
Background: Gastric ulcer is common and serious diseases caused by imbalances between naturally occurring defensive factors such as mucus, prostaglandins and aggressive factors such as hydrochloric acid, usually found in gastrointestinal juices